Aztec history, colonial heroes: reimagining the Mexica-Chalca War in early New Spain. - Villella, Peter B. (Colonial Latin American Review, 2025)
This essay addresses how colonial writers in Spanish-ruled Mexico repurposed memories of the pre-colonial Aztec world they encountered via Nahua historical knowledge and its associated texts. The essay focuses on accounts produced between approximately 1580 and 1625 of an important fifteenth-century conflict between the Mexica Empire and the independent confederation of Chalco, due to its ubiquity in diverse sources and the wealth of vivid and comparable details it offers. Specifically, it inquires how genre, form, identity, and ideology influenced colonial portrayals of the war, thereby highlighting the complex heterogeneity of Novohispanic intellectual culture. Arguing against binaries between 'Indigenous' and 'Spanish' perspectives, this essay shows how Nahua historiographical traditions and ethnopolitical distinctions, contrasting strategies of Christian evangelization, and the imposition of alphabetic writing all intersected in ways discernible in written accounts of the Chalco conflict from that period. By the seventeenth century, erudite colonial historiography—and, subsequently, colonial-era perceptions of the Aztec past—was evolving in alignment with central Mexican urban society more generally: extraordinarily diverse and rapidly transforming along several axes, including belief, literacy, and ethnicity.